Evaluación antibacteriana de extracto de mosquera (Croton elegans.) frente a: (Staphylococcus aureus ATCC: 25923, Streptococcus pyogenes ATCC: 19615, Streptococcus pneumoniae ATCC: 49619 y Streptococcus mutans ATCC: 25175), patógenos de enfermedades respiratorias - Ordóñez Rea, Omar Leonardo (2016)
In our country there is a variety of medicinal plants some of them without scientific studies and little investigation that is the case of the species Croton elegans, the ethnobotanical use of it allows us to deduce some antimicrobial activity, this being the fundament that determined the essay on some respiratory disease causing bacteria such as: Staphylococcus aureus ATCC 25923 Streptococcus pneumoniae ATCC (49619), Streptococcus mutans ATCC (25175) y Streptococcus pyogenes ATCC (19615). Maceration with dry crushed leaves in 90% alcohol was performed for two days and a fluid extract was obtained in two concentrations 25% and 50%. With the extracts, phytochemical qualitative and antimicrobial activity tests were performed by the modified well diffusion method. The obtained results in the phytochemical tests show presence of resins, amino acids, flavonoids, catechins, alkaloids, quinones. The antibacterial activity tests on either extract concentrations showed no activity against Staphylococcus aureus ATCC 25923, in the case of Streptococcus pneumoniae ATCC 49619, both concentrations presented with inhibitory activity, the statistical analysis determines that a 50% concentration is more effective with a halo of 11.74 mm, with Streptococcus mutans ATCC 25175, both concentrations had inhibitory activity, but statistically neither concentration showed more effectiveness above the other, in Streptococcus pyogenes ATCC 19615, both concentrations had inhibitory activity, statistically concentration 25% was more effective with a halo of 15.16 mm.